Penggunaan Enzim Untuk Kosmetik - Aida Soelaeman (Jurnal Kimia dan Kemasan, 1989)
Enzym are complex, colloidal organic catalysts produced by living cells, but unabl eto produce themselves. They occur in animal and plant life, and around 20,000 to 30,000 enzyme are beli ved to exist in the human body. In cosmetic application enzyme is also needed, for instance enzyme for skin care which can be produce from vegetables and fruits such as trypsine, lipase, diastase, bromelin, papain, and enzyme for skin treatment which can be used urease, pepsin, catalase, trypsine. Besides, urease and catalase are useful also for dentifrices and hair care.